World Crisis and Protecting Low-Income Countries Against Exogenous Shocks - Patrick Guillaumont (Fondation pour les études et recherches sur le développement international (FERDI), 2009)
Developing countries, specifically low-income countries, and above all least developed countries, are facing recurrent shocks. While the resources available to the international community to help them cope with such shocks have long been debated, the world economic crisis sheds new light on the problem. There is a risk that the shocks may take on unprecedented proportions, which will bring to light the gaps in the international protection system. This situation gives us an opportunity to consider reforms to this system.
Keywords: G01; 330